5 - Perception du Centre d’Observation des Mineurs (COM) d’Abidjan par les Minuers Incarceres et Persistance dans les Actes Antisociaux - Zeze Marie-Thérèse Dahonnon; Niamke, Jean Louis (African Sociological Review, 2022)
The objective of this study is to analyze the explanatory factors of the recidivism of minors incarcerated at the Juvenile Observation Center in Abidjan. The methodology used is a two- pronged approach, one quantitative and the other qualitative. Observation, documentary research and interviewing were used as techniques for gathering information. The results indicate that the recidivism of juveniles incarcerated in the COM is related to various aspects of incarceration such as long-term child detention, the depreciating quality of treatment in relation to the inappropriate prison location for the resocialization of adolescents, and the asymmetrical relationships that minors have with their educators. This study makes it possible to understand scientifically that the treatment of minors incarcerated in the COM by the juvenile protection justice in Ivory Coast, difficult to find strategies adapted and in line with the realities of adolescents on the margins of a generally uprooted society.